Direct Age Discrimination of Older and Young Employees in The Scientific and Higher Education System of The Republic of Croatia (Vallis Aurea, 2021)
Age discrimination comes to the fore at all stages of the employment process and can imply a number of negative consequences for both young and older people.The goal of this paper is to check the existence of direct age discrimination of older and young workers in the hiring process in the system of science and higher education of the Republic of Croatia. The paper should answer the questions of whether and to what extent respondents have ever personally experienced discrimination in employment by being told or written that they are too young or too old.In order to achieve the said goal, an empirical research was conducted, and employees of two Croatian universities were selected for the research group: Josip Juraj Strossmayer University of Osijek and the University of Rijeka.Data collection was conducted using an onlinequestionnaire posted on the Google Drive platform between May 29 and June 21, 2017. The list of contacts and e-mail addresses of the respondents were obtained from the official websites of the constituent universities and theirRectors’ offices, and a total of 2958 addresses were identified: 1506 at the University of Rijeka and 1452 addresses at the Josip Juraj Strossmayer University in Osijek.The empirical research results indicated the following:1. 12.97% of respondents experienced direct age discrimination in the hiring process by being told/informed in writing that they were too young 2. 7.52% of respondents experienced direct age discrimination in the hiring process by being told/informed in writing that they were too old 3. there is a statistically significant difference between respondents with regard to age. Elderly respondents were more likely to experience direct age discrimination by being told/informed in writing that they were too old 4. there is a statistically significant difference between respondents with regard to years of service. Respondents who were told/informed in writing in the hiring process that they were too old on average have more years of work experience (21,05 years) than those who were not told/informed in writing (15, 47 years)